Rage and carnage in the name of God religious violence in Nigeria - Alao, Abiodun 1961- (Duke University Press, 2022)
In Rage and Carnage in the Name of God, Abiodun Alao examines the emergence of a culture of religious violence in postindependence Nigeria, where Christianity, Islam, and traditional religions have all been associated with violence. He investigates the root causes and historical evolution of Nigeria's religious violence, locating it in the forced coming together of disparate ethnic groups under colonial rule, which planted the seeds of discord that religion, elites, and domestic politics exploit. Alao discusses the histories of Christianity, Islam, and traditional religions in the territory that became Nigeria, the effects of colonization on the role of religion, the development of Islamic radicalization and its relation to Christian violence, the activities of Boko Haram, and how religious violence intermixes with politics and governance. In so doing, he uses religious violence as a way to more fully understand intergroup relations in contemporary Nigeria
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2022)
Keywords: HISTORY / Africa / West; Intergroup relations -- Nigeria; Religion and culture -- Nigeria; Religion and politics -- Nigeria; Violence -- Nigeria -- Religious aspects; Gewalttätigkeit; Religion; Nigeria